2021
DOI: 10.3390/genes12081292
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Piwi, MMP, TIMP, and Sox during Gut Regeneration in Holothurian Eupentacta fraudatrix (Holothuroidea, Dendrochirotida)

Abstract: Mesodermal cells of holothurian Eupentacta fraudatrix can transdifferentiate into enterocytes during the regeneration of the digestive system. In this study, we investigated the expression of several genes involved in gut regeneration in E. fraudatrix. Moreover, the localization of progenitor cells of coelomocytes, juvenile cells, and their participation in the formation of the luminal epithelium of the digestive tube were studied. It was shown that Piwi-positive cells were not involved in the formation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Four hemopexin-like repeats are located after the catalytic domain. The second, 47 kDa (GHCL01010993.1), is Ef-MMP16 [ 79 ]. This is a furin-activatable MMP.…”
Section: Matrix Metalloproteinases Of Echinodermsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four hemopexin-like repeats are located after the catalytic domain. The second, 47 kDa (GHCL01010993.1), is Ef-MMP16 [ 79 ]. This is a furin-activatable MMP.…”
Section: Matrix Metalloproteinases Of Echinodermsmentioning
confidence: 99%
“…Its propeptide domain does not contain PGBD, and four hemopexin-like repeats are located at the C-terminus. It was shown that Ef-MMP16 expresses during gut regeneration in holothurian E. fraudatrix [ 79 ]. Its transcripts were found in the coelomic epithelium of the mesentery and gut anlage.…”
Section: Matrix Metalloproteinases Of Echinodermsmentioning
confidence: 99%
See 3 more Smart Citations